2011
DOI: 10.1002/elps.201100230
|View full text |Cite
|
Sign up to set email alerts
|

The effect of miR‐7 on behavior and global protein expression in glioma cell lines

Abstract: Malignant glioma is a common cancer of the nervous system. Despite recent research efforts in cancer therapy, the prognosis of patients with malignant glioma has remained dismal. MicroRNAs are noncoding RNAs that inhibit the expression of their targets in a sequence-specific manner, and a few have been shown to act as oncogenes or tumor suppressors. Here, we aimed at exploring the precise biological role of microRNA-7 (miR-7) and the global protein changes in glioma cell lines transiently transfected with miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The expression of Anxa4 was inhibited by miR-7 overexpression in glioma cells, miR-7 overexpression inhibited migration and invasion capacities of glioma cell lines U251, U87, and A172 reduced the tumorigenicity and metastasis of U251 cells in nude mice [71]. Proteomic analysis demonstrated that Anxa4 was decreased 3.5-fold in miR-7 overexpressed U251 cells compared with control group [71].…”
Section: Anxa4 and Gliomamentioning
confidence: 95%
“…The expression of Anxa4 was inhibited by miR-7 overexpression in glioma cells, miR-7 overexpression inhibited migration and invasion capacities of glioma cell lines U251, U87, and A172 reduced the tumorigenicity and metastasis of U251 cells in nude mice [71]. Proteomic analysis demonstrated that Anxa4 was decreased 3.5-fold in miR-7 overexpressed U251 cells compared with control group [71].…”
Section: Anxa4 and Gliomamentioning
confidence: 95%
“…MicroRNAs (miRNAs) that regulate 14-3-3ζ have been reported in the literature. In glioma cells, the over-expression of microRNA-7 (miR-7) down-regulated 14-3-3ζ [14]. In K562 cells, up-regulated expression of microRNA-375 (miR-375) was associated with down-regulated expression of 14-3-3ζ [15].…”
Section: Introductionmentioning
confidence: 99%
“…2-DE was performed as described previously [8]. Briefly, cells were lysed in lysis buffer (8M urea, 2M thiourea, 4% CHAPS, 100mM DTT, 0.2% pH 3-10 ampholyte, BioRad, Hercules, CA) containing 1% protease inhibitor cocktail 8340 (104 mM AEBSF, 80 μM Aprotinin, 4 mM Bestatin, 1.4 mM E-64, 2 mM Leupeptin, 1.5mM Pepstatin A) (Sigma, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%